Fluorescence in situ hybridization (FISH) and cell sorting of living bacteria - Batani, Giampiero; Bayer, Kristina; Böge, Julia; Hentschel, Ute; Thomas, Torsten (Scientific reports, 2019)
Despite the development of several cultivation methods, the rate of discovery of microorganisms that are yet-to-be cultivated outpaces the rate of isolating and cultivating novel species in the laboratory. Furthermore, no current cultivation technique is capable of selectively isolating and cultivating specific bacterial taxa or phylogenetic groups independently of morphological or physiological properties. Here, we developed a new method to isolate living bacteria solely based on their 16S rRNA gene sequence. We showed that bacteria can survive a modified version of the standard fluorescence in situ hybridization (FISH) procedure, in which fixation is omitted and other factors, such as centrifugation and buffers, are optimized. We also demonstrated that labelled DNA probes can be introduced into living bacterial cells by means of chemical transformation and that specific hybridization occurs. This new method, which we call live-FISH, was then combined with fluorescence-activated cell sorting (FACS) to sort specific taxonomic groups of bacteria from a mock and natural bacterial communities and subsequently culture them. Live-FISH represents the first attempt to systematically optimize conditions known to affect cell viability during FISH and then to sort bacterial cells surviving the procedure. No sophisticated probe design is required, making live-FISH a straightforward method to be potentially used in combination with other single-cell techniques and for the isolation and cultivation of new microorganisms.
Keywords: Cell Separation; DNA sondy; bakteriální RNA; Phylogeny; RNA, Ribosomal, 16S; hybridizace in situ fluorescenční; separace buněk; Bacillus; mikrobiologické techniky; DNA Probes; In Situ Hybridization, Fluorescence; fylogeneze; Flow Cytometry; Bacteria; RNA, Bacterial; průtoková cytometrie; RNA ribozomální 16S; Microbiological Techniques